Pelatihan Pembuatan Arang Briket dengan Pemanfaatan Limbah Batok Kelapa di Desa Pangpong - Anggraini, Yunita; Ariyanti, Amelia Siti; Putra, Robby Pratama; Zakiyah, Fitriyatuz (Jurnal Solutif: Jurnal Pengabdian Masyarakat, 2024)
The aim of carrying out this community service is to provide an understanding of the importance of coconut shell briquette charcoal as an alternative fuel which is usually used for cooking, especially for grilling food, to train Pangpong Village residents in providing training on the process of making charcoal briquettes to the Pangpong Village community through 3 stages, namely the preliminary stage, socialization stage, and final evaluation stage. It is hoped that this program can run well and increase the insight of the people of Pangpong Village, Labang District, Bangkalan Regency. The results of this training program are to increase public understanding about making coconut shell charcoal briquettes and the output is expected to be published in community service journals.